Comparative Assessment of Thermal Treatment for Mycotoxins Adsorption Potential of Indigenous Clay from Balochistan, Pakistan - Mustafa Rahim Abro; Nadeem Rashid; Rab Nawaz Soomro; Khanoranga; Zainab Siddique (Pakistan Journal of Analytical & Environmental Chemistry)
The current study aimed to investigate the physical characteristics and mycotoxins (Aflatoxins B1 (AFB1) and Ochratoxin A (OTA) binding efficacy of indigenous clays before and after thermal treatment (calcination). The clay sample was collected from various mountainous areas of Balochistan, Pakistan. The samples were ground into a 360 mesh size and thermally treated initially at 200 °C and thereafter at 800 °C for 30 minutes with the help of a muffle furnace. XRD analysis revealed montmorillonite as the most commonly occurring group of clay minerals. The thermally treated clays showed that the binding potential was significantly (P <0.05) improved against mycotoxins. Enzyme-linked immunoassay (ELISA) determination showed significantly (P <0.05) lower residual concentrations of mycotoxins in thermally treated clays. The mycotoxin adsorption capacity (%) was found to be higher in the clay samples procured from Pishin (79.17% for AFB1 and 67.34% for OTA) and Bolan (62.0% for AFB1 and 50.17% for OTA). Calcination also caused a significant decrease in Cation Exchange Capacity (CEC) in some clay samples. Overall, the findings of the study showed that thermal treatment enhanced the in vitro binding capacity of clays against the studied mycotoxins. An increase in the mycotoxin binding capacity of the clays not only reduces the bioavailability of mycotoxins but also decreases their toxic effects. It is recommended that Balochistan clay have the potential to be used as an adsorbent for the removal of mycotoxins from the environment and animal feeds